Approach to Analyze and Design V Shaped Beams - Wala, Aqeel Ali Shams Wagla (AMC Indian Journal of Civil Engineering, 2022)
This instructional paper emphasizes on a very common structural situation faced by designers, how to approach the analysis of a V shaped or corner beams. In this paper, an example is solved first using SAP2000 and then manually implementing appropriate theory for such a problem. This paper not only covers analysis of V shaped beams but also explains the approach taken by FEM software for the same.